Integrating Public Participation, Transparency and Accountability Into Governance of Marketing Authorisation for Genome Editing Products - Nielsen, Jane; Eckstein, Lisa; Nicol, Dianne; Stewart, Cameron (Frontiers in Political Science, 2021)
Public participation, transparency and accountability are three of the pillars of good governance. These pillars become particularly important for innovative, personalised health technologies, because of the tendency of these technologies to raise distinct scientific, ethical, legal and social issues. Genome editing is perhaps the most personal of all innovative health technologies, involving precise modifications to an individual’s genome. This article focuses on the adequacy of current requirements for public participation, transparency and accountability in the governance of the market authorisation for genome edited products. Although clinical trials for genome edited products are only just underway, lessons can be drawn from the marketing approvals pathways for related gene therapy products. This article provides a broad overview of the regulatory pathways that have been adopted by the US Food and Drugs Administration, the European Medicines Authority, and the Australian Therapeutic Goods Administration for reviewing gene therapy products for marketing approval. This analysis focuses on the extent to which public participation processes and transparency and accountability of review pathways are incorporated into marketing approval policy and practice. Following this review, the article proposes the application of Sheila Jasanoff’s “technologies of humility” as a foundation for meaningfully incorporating these pillars of good governance into regulatory processes for the review of products of genome editing. We conclude by articulating clear mechanisms for operationalising technologies of humility in the context of public participation, transparency and accountability, providing a blueprint for future policy development.